ANALISIS USAHA OLAHAN IKAN BELIDA (Notopterus chitala) DAN IKAN PATIN (Pangasius sp) DI DESA JANTUR KECAMATAN MUARA MUNTAI KABUPATEN KUTAI KARTANEGARA - Novia, Novia; Saleha, Qoriah; Erwiantono, Erwiantono (Journal of Fisheries and Marine Applied Science, 2024)
This study aims to determine the stages of processing crackers and amplang from belida fish and patin fish in Jantur Village, Muara Muntai Subdistrict by analyzing the feasibility of businesses run by 8 respondents. The research method used is qualitative and quantitative, using a questionnaire to conduct structured interviews.  Data sample collection was carried out using the census and survey methods and then analyzed descriptively and calculated the sales costs and profits of processed belida and catfish businesses. The processing cycle of belida fish crackers, amplang belida fish, and catfish crackers is 1-6 times/production year (average 3 production cycles/year). The average profit obtained from the belida fish cracker processing business is Rp.1,042,234 / year. The average profit obtained from the belida fish amplang processing business is Rp.2,744,869 / year and the average profit obtained from the patin fish cracker processing business is Rp.59,133 / year. This business feasibility analysis results show that processing belida fish and catfish is still often run even though it takes longer to reach the return on investment.